2022
DOI: 10.1186/s12864-022-09007-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic response to ISAV infection in the gills, head kidney and spleen of resistant and susceptible Atlantic salmon

Abstract: Background Infectious Salmon Anaemia virus (ISAV) is an orthomyxovirus responsible for large losses in Atlantic salmon (Salmo salar) aquaculture. Current available treatments and vaccines are not fully effective, and therefore selective breeding to produce ISAV-resistant strains of Atlantic salmon is a high priority for the industry. Genomic selection and potentially genome editing can be applied to enhance the disease resistance of aquaculture stocks, and both approaches can benefit from incre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…In our study, we observed an increase in RPL17 and GIMAP7 in the infected RHTiB cells at 24 hpi. The phosphorylation of these proteins is associated with the concentration of infectious salmon anemia virus in the head kidney of infected salmon 81 , whereas the phosphorylation of GIMAPs plays a crucial role in the antiviral response in zebrafish 82 . These findings suggest that TiLV modulates the host immune response and promotes significant viral replication in RHTiB cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed an increase in RPL17 and GIMAP7 in the infected RHTiB cells at 24 hpi. The phosphorylation of these proteins is associated with the concentration of infectious salmon anemia virus in the head kidney of infected salmon 81 , whereas the phosphorylation of GIMAPs plays a crucial role in the antiviral response in zebrafish 82 . These findings suggest that TiLV modulates the host immune response and promotes significant viral replication in RHTiB cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, transcriptome analysis has been used to characterise gene expression patterns involved in immune responses to microbial infections, e.g., detecting pilchard orthomyxovirus, a virus of vital concern in Tasmania (Samsing et al 2022). Such approaches can be used to examine physiological responses to abiotic and biotic stressors (Alipio et al 2022, Gervais et al 2022, determine optimal rearing conditions for promoting immunocompetence (Ellison et al 2020), help reduce disease outbreaks, (Ajasa et al 2024) and develop more efficacious vaccines against infection (Fu et al 2022). Genetic techniques also have demonstrated that quantifying hormone expression can guide the determination of optimal stocking densities, by using peptide hormones as biomarkers to analyse the physiological response of Atlantic salmon to population densities (Alvarez et al 2022).…”
Section: Genetic Considerationsmentioning
confidence: 99%